P1.025 Effects of Abnormal Vaginal Flora and Menopause on Cervicovaginal Fluid Viscosity. (13th July 2013) - Chappell, C A; Rohan, L C; Wang, L; Meyn, L; Moncla, B J; Bunge, K; Hillier, S L
Abstract : Background: Sexually transmitted pathogens, including HIV, are increased among women having abnormal vaginal flora. The mucus gel layer is a component of innate mucosal immunity, and the presence of mucus may contribute to the viscosity of genital tract fluid. Little is known about the impact of reproductive hormones, menopause and vaginal flora patterns on the viscosity of cervicovaginal fluid. Methods: Vaginal swabs and cervicovaginal lavage (CVL) were collected from 134 healthy asymptomatic post-menopausal women (n = 23), women in the follicular (n = 26) or proliferative (n = 19) phase, and women using levonogerestrol IUDs (n = 28), DMPA (n = 13) or combined oral contraceptives (n = 25). Vaginal smears were evaluated using the Nugent criteria. The viscosity (centipoise, cP) of each sample was measured in triplicate using a Cambridge MicroSample Viscometer. Student's t-test, analysis of variance, and linear regression were used to assess statistical significance. Results: The mean CVL viscosity among the 84 women having a Nugent score < 4 was 1.51(± 0.48) vs. 1.26(± 0.29) cP for the 50 women with abnormal vaginal flora (p = 0.001). There was no difference in CVL viscosity for women with intermediate vs. BV flora (p > 0.99). Similarly, there was no difference in viscosity among women at different phases of their menstrual cycle, nor among women using different hormonal contraceptive methods. However, the CVL of 23 postmenopausal women was less viscous compared to the 111 premenopausal women, 1.16(± 0.26) vs. 1.47(± 0.44) cP respectively (p = 0.001). In a linear regression model, abnormal flora (p = 0.01) and postmenopausal status (p = 0.005) were independently associated with decreased CVL viscosity. Conclusion: Abnormal flora and being post-menopausal are independently associated with decreased CVL viscosity. Even though phase of menstrual cycle and hormonal contraceptive use has been posited to have an impact on cervical mucus, these data suggest that these factors do not have a measurable impact of vaginal fluid viscosity.